(untitled) (Conferencea, 2023)
This article describes the means of prevention of subclinical ketosis in cows, their effect on clinical and hematological parameters. In the prevention of subclinical ketosis in productive cows, LPP-1 vitamin-mineral premix 40 g per head per day, 1.5 g of sodium bicarbonate per head, 20 g of sodium bicarbonate per head per day, and the effectiveness of giving it in the 1-3 months of lactation are high. improves and increases the functional state of metabolism and liver and prevents subclinical ketosis.